Analysis Of The Influence Of Community Perception And Community Participation In Corporate Social Responsibility (CSR) Activities On Company Images Of Minarak Brantas Gas, Inc. - John Basuki Rahmad; Didit Herawan (Jurnal Scientia, 2024)
This research aims to determine the influence of Community Perception and Community Participation on the Implementation of Corporate Social Responsibility (CSR) Activities and its impact on Company Image. This type of research is quantitative descriptive research. This research was located in Kalidawir village and Kedung Banteng village, Tanggulangin sub-district, Sidoarjo district. The population in this study were community members who received the Minarak Brantas Gas, Inc. CSR program. The sampling technique in this research uses a probability sampling technique or opportunity sampling with a simple random sampling method. The results of the analysis also show that there is a significant direct influence of community participation in CSR activities (X2) on the implementation of CSR activities (Z) with a significance t variable X2 of 0.000 (< 0.05). Other results show that there is a significant direct influence on public perception of CSR activities (X1) on the company's image (Y) with a significance t variable X1 of 0.000 (< 0.05); there is a significant direct effect of community participation in CSR activities (X2) on the company's image (Y) with a significance t variable X2 of 0.000 (< 0.05); and there is a significant direct influence of the implementation of CSR activities (Z) on the company's image (Y) with a significance t variable Y of 0.000 (< 0.05). The results of the indirect influence test show that there is a significant indirect influence on public perception of CSR activities (X1) on the company's image (Y) through the implementation of CSR activities (Z) with a significance variable X1 on Y through Z of 0.013 (< 0.05) ; and there is a significant indirect effect of community participation in CS R activities (X2) on the company's image (Y) through the implementation of CSR activities (Z) with a significance variable X2 on Y through Z of 0.000 (< 0.05).